Preservation of Pleural Integrity during Coronary Artery Bypass Surgery Affects Respiratory Functions and Postoperative Pain: A Prospective Study - Bilgehan Savas Oz; Hikmet Iyem; Hakki Tankut Akay; Vedat Yildirim; Kubilay Karabacak; Cengiz Bolcal; Ufuk Demirkiliç; Harun Tatar (Canadian Respiratory Journal)
OBJECTIVE: To evaluate the role of preserved pleural integrity in postoperative pain and respiratory functional status in patients undergoing coronary revascularization.